DAGESTAN IN THE STRUGGLE OF THE PEOPLES OF THE NORTH-EAST CAUCASUS AGAINST FOREIGN INVADERS IN THE 15TH CENTURY - Murtazaev, A O; Magaramov, S A (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the struggle of the peoples of Dagestan against foreign invaders in the 15th century, in particular, against Turkic tribal federation Kara Koyunlu formed after the collapse of Ilkhanate, as well as the Shiite religious order of the Safavids. The authors of the article consider the reasons, purpose, and effects of the first campaigns of the Safavid troops in Dagestan.
Keywords: invasion; struggle; Kara Koyunlu; help; Dagestan; Shirvan; Qara Yusuf; Iskander; Shirvanshah; Junayd; Heidar; Safavids; Ardabil